Imatinib Sets Pericyte Mosaic in the Retina - Tamás Kovács-Öller (International Journal of Molecular Sciences, 2020)
The nervous system demands an adequate oxygen and metabolite exchange, making pericytes (PCs), the only vasoactive cells on the capillaries, essential to neural function. Loss of PCs is a hallmark of multiple diseases, including diabetes, Alzheimer’s, amyotrophic lateral sclerosis (ALS) and Parkinson’s. Platelet-derived growth factor receptors (PDGFRs) have been shown to be critical to PC function and survival. However, how PDGFR-mediated PC activity affects vascular homeostasis is not fully understood. Here, we tested the hypothesis that imatinib, a chemotherapeutic agent and a potent PDGFR inhibitor, alters PC distribution and thus induces vascular atrophy. We performed a morphometric analysis of the vascular elements in sham control and imatinib-treated NG2-DsRed mice. Vascular morphology and the integrity of the blood–retina barrier (BRB) were evaluated using blood albumin labeling. We found that imatinib decreased the number of PCs and blood vessel (BV) coverage in all retinal vascular layers; this was accompanied by a shrinkage of BV diameters. Surprisingly, the total length of capillaries was not altered, suggesting a preferential effect of imatinib on PCs. Furthermore, blood–retina barrier disruption was not evident. In conclusion, our data suggest that imatinib could help in treating neurovascular diseases and serve as a model for PC loss, without BRB disruption.